Enhanced Dielectric Loss and Magnetic Loss Properties of Copper Oxide-Nanowire-Covered Carbon Fiber Composites by Porous Nickel Film - Zeng, Jun; Zhang, Shiquan; Xue, Jun; Dai, Huili; Xia, Long; Cai, Wenyanhong; Tang, Yanhua; Xu, Chaoyi (Frontiers in Materials, 2020)
The porous nickel film with agglomerate nanoparticles and 1.5~2.0 μm in thickness was used to enhance microwave absorption and ferromagnetic properties of nanowire-like copper oxide-covered carbon fiber composites. Firstly, the porous nickel film/carbon fiber composites were prepared by plating route, when the current intensity was 120 mA for 30 min (sample S1) and 40 min (sample S2), respectively. Then, the copper oxide/porous nickel/carbon fiber (CNCF1 and CNCF2) composites were synthetized by electroless deposition copper and thermal oxidation route (the sample S1 and sample S2), respectively. The microwave absorption properties of composites were investigated over frequency range, 1-18 GHz. The results showed that the strongest reflectivity loss (RL) values of CuO/carbon fiber (CCF) and CNCF1-2 composites were -25.93 dB at 3.59 GHz with a matching thickness layer of 2.4 mm, -27.87 dB at 6.67 GHz with a matching thickness layer of 2.5 mm, and -54.82 dB at 9.23 GHz with a matching thickness layer of 2.192 mm. When the RL values of CCF and CNCF1-2 composites were lower than -10 dB, the absorption frequency range from 8.12 to 9.64 GHz (1.52 GHz in absorption bandwidths, 1.5 mm in thickness), 6.45 to 8.81 GHz (2.36 GHz in absorption bandwidths, 2.4 mm in thickness) and 10.51 to 14.35 GHz (3.84 GHz in absorption bandwidths, 1.8 mm in thickness), respectively. Therefore, the CNCF2 composites showed more excellent microwave absorption properties, and are potential microwave absorption candidates for making a thin thickness, strong absorption and wide-frequency.